Difficulties in urgent and emergency care in small municipalities: Literature review - Moura, Edenílson Leonardo Vendrameto de; Sanguino, Gabriel Zanin; Frez , Flávia Cristina Vieira; Sesnik, Heitor Hortensi; Felipin, Larissa Carolina Segantini; Santos , Lorraine de Souza; Lima , Ana Luísa Serrano; Fernandes, Maria Eduarda Itikawa; Iamaguchi, Franciele Emily; Luz, Kelly Cristina Suzue Iamaguchi (Seven Editora, 2023)
The objective of this study was  to point out the difficulties faced in urgent and emergency care for critically ill patients in small municipalities, according to the current literature. This is a bibliographic research, with a qualitative, retrospective approach, of a basic nature, with the exploratory purpose of data, having as a data source articles published between the years 2006 and 2021. From February to November 2021, 576 articles were collected, but only 13 met the inclusion criteria, and 563 articles were discarded. The results were separated into axes. Axis 1 grouped articles that discuss the management and conditions of the urgency and emergency service in small municipalities. Axis 2 describes elements that identify and report all the difficulties faced by nurses on a daily basis in the urgent and emergency service. Axis 3, on the other hand, contains the reports that express all the feelings of stress and suffering experienced in the hospital environment. The first axis is headed for 3 articles, the second axis is 7 for articles and the third axis is for 3 articles. The difficulties faced by small municipalities involve issues related to the physical structure, the excessive demand for work that could be reviewed and distributed among the less complex services, and the feelings generated by the obstacles experienced, such as the work overload that causes stress. DOI:https://doi.org/10.56238/sevened2023.004-006